Na militância para o reconhecimento: um estudo de mulheres negras ativistas na cidade de São Paulo - Barbosa, Eliete Edwiges (2015)
This research deals with the activism of women as leaders of social movements, taking into account the similarities and differences across their ethnic conditions (black and not black), militancy period and type of social movement. For this analysis, we used the concept of "active minorities" S. Moscovici, who believes that, alongside mechanisms of social conformity, there are also values of dispute processes. Social movements are seen, as well as defense of spaces and their leaders as active minorities. In this theoretical framework, we contextualize the feminist movement in Brazil was made, emphasizing the internal contradictions in the light of black ethnicity